Negation and social avoidance in language recruits the right inferior frontal gyrus: a tDCS study - Enrique García-Marco; Enrique García-Marco; Aarón Nuez Trujillo; Iván Padrón; Iván Padrón; Yennifer Ravelo; Yennifer Ravelo; Yang Fu; Yang Fu; Hipólito Marrero; Hipólito Marrero (Frontiers in Psychology, 2024)
IntroductionIn the process of comprehension, linguistic negation induces inhibition of negated scenarios. Numerous studies have highlighted the role of the right Inferior Frontal Gyrus (rIFG) - a key component of the inhibitory network - in negation processing. Social avoidance can be linguistically portrayed using attitudinal verbs such as “exclude” vs. “include”, which inherently carry negative connotations. Consequently, we hypothesize that the interplay between explicit negation and the implicit negativity of avoidance verbs can be modulated via transcranial direct current stimulation (tDCS) targeting the rIFG.MethodsIn our study, sixty-four participants read approach/avoidance sentences, which were either affirmative or negative, such as “Anne included (did not include) meat in her diet” vs. “Anne excluded (did not exclude) meat in her diet”. This reading task followed a 20-minute tDCS session. The sentences were sequentially displayed, and at 1500 ms post-sentence, a verb was shown – either the one previously mentioned or its semantic alternative counterpart (e.g., included vs. excluded).ResultsFindings revealed that anodal stimulation intensifies the inhibitory impact of negation during sentence comprehension. Under anodal conditions, negative sentences led to extended reading times for the mentioned verbs compared to their affirmative counterparts, suggesting an increased inhibitory effect on the verb. Furthermore, in avoidance sentences, anodal stimulation resulted in reduced reading times for alternative verbs (e.g. “included”) in negative sentences compared to alternative verbs (e.g. “excluded”) in negated approach sentences.DiscussionAs “avoidance” is semantically equivalent to “non-approach”, the inhibitory effect of negation is primarily applied to the implicit negation: NOT EXCLUDED = NOT→NOT (INCLUDED), which consequently activates the representation of the alternative verb making it more available. We further discuss these findings in light of the rIFG’s pivotal role in processing attitudinal verbs and linguistic negation. This discussion is framed within the overarching context of the two-step model of negation processing, highlighting its significance in the realm of social communication.